Идентификация сосредоточенного нестационарного воздействия на бесконечную пластину-полосу - Янютин, Евгений Григорьевич; Кучерова, Н. И. (НТУ "ХПИ", 2008)
Розглянуто рішення прямої та оберненої нестаціонарних задач для нескінченої пластини-полоси. Досліджується дія на пластину імпульсного навантаження. Пластина-полоса моделюється теорією Кирхгофа-Лява. При розв’язку інтегрального рівняння Вольтерра застосовується метод А. С. Апарцина.

Solutions of direct and inverse non-stationary problems for infinite plate-strip are considered. An impulse load action on plate is explored. The simulation of the plates-strip deforming is based on classic Kirchhoff’s theory. The Volterra integral equations are solved by using Aparcin's method.
Keywords: нагружение; импульсные воздействия; поперечные колебания пластины; преобразование Лапласа; преобразование Фурье; теория Кирхгофа-Лява